2021
DOI: 10.1111/jsr.13300
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic nightmares: Effects on dream activity of the COVID‐19 lockdown in Italy

Abstract: COVID-19 has critically impacted the world. Recent works have found substantial changes in sleep and mental health during the COVID-19 pandemic. Dreams could give us crucial information about people's well-being, so here we have directly investigated the consequences of lockdown on the oneiric activity in a large Italian sample: 5,988 adults completed a web-survey during lockdown. We investigated sociodemographic and COVID-19-related information, sleep quality (by the Medical Outcomes Study-Sleep Scale), menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
157
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(205 citation statements)
references
References 42 publications
33
157
0
2
Order By: Relevance
“…Further, a gender difference was observed since females revealed a larger dream recall rate according to the previous literature (e.g., Barrett, 2020;Iorio et al, 2020;Scarpelli et al, 2021a). In addition, aging was associated with a drop in dream recall frequency also during lockdown (Scarpelli et al, 2021a).…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Further, a gender difference was observed since females revealed a larger dream recall rate according to the previous literature (e.g., Barrett, 2020;Iorio et al, 2020;Scarpelli et al, 2021a). In addition, aging was associated with a drop in dream recall frequency also during lockdown (Scarpelli et al, 2021a).…”
Section: Introductionmentioning
confidence: 55%
“…Awakenings during sleep would guarantee the elaboration of dream material and its transfer from short-term memory storage to long-term storage (Koulack and Goodenough, 1976;Scarpelli et al, 2021b). Interestingly, NT1 patients, as well as control subjects (see Scarpelli et al, 2021a) reported an association between frightening dreams and higher sleep duration. This finding is only apparently in conflict with the activation/arousal-retrieval model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a shift toward more negative dreams was found, which was directly related to the subjective stress in waking life, for example, social distancing affected mental health (Barrett, 2020;Iorio et al, 2020;Mota et al, 2020;Schredl and Bulkeley, 2020). In a similar way, the frequency of nightmares increased during the pandemic in both clinical (Gupta, 2020;Sierro et al, 2020) and normative samples of adults (Musse et al, 2020;Pérez-Carbonell et al, 2020;Scarpelli et al, 2021).…”
Section: Introductionmentioning
confidence: 80%